1960
DOI: 10.1111/j.1365-2621.1960.tb00022.x
|View full text |Cite
|
Sign up to set email alerts
|

BROWNING OF SUGAR SOLUTIONS. IV. THE EFFECT OF PH ON THE VOLATILE PRODUCTS OF REDUCING SUGARSa

Abstract: The principal steam volatile carbonyl compounds obtained from the alkaline decomposition of reducing sugars are generally considered to be methylglyoxal and acetol. These compounds have also been suggested as browning intermediates (22,23). It is still doubtful, however, as to which of these two compounds represents the major product formed in the reaction. Fernbach and Schoen (7), Fischler (8,9), E vans (6), and Enders (3, 4, 5) have implicated methylglyoxal on the basis of the isolation of its phenylosazone.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

1960
1960
2012
2012

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 16 publications
1
4
0
Order By: Relevance
“…This formed constituent is no doubt methylglyoxal since it has been shown by earlier work in this laboratory (8) that the formation of methylglyoxal from these two triose sugars is increasingly favored as the pH is decreased to 4. Previous work here (8) has also shown that as the pH of solutions of these two sugars is decreased below 7 little or no acetol is formed. This indicates that methylglyoxal is being formed and that it is involved in the acid browning of dihydroxyacetone and of glyceraldehyde.…”
Section: Resultssupporting
confidence: 54%
See 1 more Smart Citation
“…This formed constituent is no doubt methylglyoxal since it has been shown by earlier work in this laboratory (8) that the formation of methylglyoxal from these two triose sugars is increasingly favored as the pH is decreased to 4. Previous work here (8) has also shown that as the pH of solutions of these two sugars is decreased below 7 little or no acetol is formed. This indicates that methylglyoxal is being formed and that it is involved in the acid browning of dihydroxyacetone and of glyceraldehyde.…”
Section: Resultssupporting
confidence: 54%
“…(ll) and Thornton and Speck (16) that in acid solution methylglyoxal is formed from dihydroxyacetone and by Nodzu et al (11) and Prey et al (13) that acetol, and by Bauer and Teed (2) and Weygand (17) that triose-reductone are formed in alkaline solutions. These findings together with work done at this laboratory (8) Laboratories as a dark brown amorphorous material which was purified by sublimation under vacuum (2 mm) at 40" C. The white sublimate was stored under nitrogen.…”
mentioning
confidence: 93%
“…Presently it is not known if the condensation and subsequent reduction of acetoin with ammonia forming tetramethylpyrazine is enzymatic. Lento et al (1960a) studied the formation of some 3-carbon carbonyl compounds from glucose and fructose heated in buffer solutions. It was suggested (Lento et al, 1960b) that acetol (hydroxyacetone) might be an important intermediate in the browning reaction at high pH levels.…”
Section: Resultsmentioning
confidence: 99%
“…This result suggests that oxidative cleavage of glucose occurs in the early stage of the bre>wning reaction. Lento et al 10 ) have reported that diacetyl was produced from glucose in strong alkaline boiling solutions, but not formed from glucose at pH 8"" 9. In the present investigation, it became clear that larger amounts of diacetyl were formed as headspace volatiles in neutral pH ranges of the amino-carbonyl reaction.…”
Section: Discussionmentioning
confidence: 99%